Characterization of Inflammatory and Fibrotic Aspects of Tissue Remodeling of Acellular Dermal Matrix in a Nonhuman Primate Model. Issue 2 (February 2021) - Ji, HaYeun; Sukarto, Abby; Deegan, Daniel; Fan, Frank
Abstract : Background: Human acellular dermal matrices (hADMs) are applied in various soft tissue reconstructive surgeries as scaffolds to support tissue remodeling and regeneration. To evaluate the clinical efficacy of hADM implants, it is integral that the hADM does not induce a host chronic inflammatory response leading to fibrotic encapsulation of the implant. In this study, we characterized the inflammatory and fibrosis-related tissue remodeling response of 2 commercial hADM products (SimpliDerm and AlloDerm RTU) in a nonhuman primate model using histology and gene expression profiling. Methods: Eighteen African green monkeys with abdominal wall defects were applied to evaluate the performance of SimpliDerm and AlloDerm RTU implants (N = 3) at 2, 4, and 12-weeks post-implantation. Using histology and gene expression profiling, tissue responses such as implant integration, degradation, cell infiltration, immune response, neovascularization, and pro-fibrotic responses over time were evaluated. Results: SimpliDerm showed a lower initial inflammatory response and slower implant degradation rate than AlloDerm RTU evidenced by histomorphological analysis. These factors led to a more anti-inflammatory and pro-remodeling microenvironment within SimpliDerm, demonstrated by lower TNFα levels and lower expression levels of pro-fibrotic markers, and promoted tissue repair and regeneration by 3-months post-implantation. Conclusions: Overall, histology and gene expression profiling analyses shown in this study demonstrated an effective model for analyzing hADM performance in terms of host inflammatory and fibrotic response. Further studies are warranted to fully evaluate the utility of this novel hADM in the clinical setting and verify the prognosis of our pre-clinical analysis model.